Estágios imaturos de Palyadini (Lepidoptera, Geometridae) e seus parasitoides associados a Myrsine umbellata Mart. (Primulaceae) em áreas de Cerrado em São Carlos, SP - Rodrigues, Elizabeth Moreira (Universidade Federal de São Carlos, 2023)
Tritrophic interactions are those that involve relationships between three trophic levels: producer, primary consumer and secondary consumer. They are considered complex, since they involve physical-chemical regulatory mechanisms, in addition to high dependence or susceptibility to each other. Thus, changes in the habitat or in other living conditions of any of these groups can cause an imbalance that will extend to the others. The Cerrado biome, the second largest biome in South America, is mainly made up of savannas. Due to human action, mainly through arson, the biome undergoes major changes, affecting many species. The species Myrsine umbellata Mart. (Primulaceae) (producer), in abundance in the Cerrado Biome, has ecological importance, being indicated for the recovery of degraded areas of grassland or secondary vegetation because it is a pioneer. The Primulaceae family, according to the literature, is closely associated with Palyadini larvae (Geometridae: Ennominae) (primary consumer), while the Hymenoptera parasitoids (secondary consumer) stand out for controlling populations of other insects that interfere with food chains. However, studies involving taxonomic and bionomic knowledge regarding the Neotropical fauna of Lepidoptera (Geometridae) and Hymenoptera parasitoids associated with the Primulaceae family are scarce. Thus, this work aimed to characterize the immature stages of Neotropical Geometridae species associated with Myrsine umbellata (Primulaceae) collected in Cerrado areas of the Federal University of São Carlos, São Carlos, SP - Brazil, aiming at the taxonomic and bionomic knowledge of the group; in order to contribute to the knowledge of the immature stages of Palyadini (Geometridae: Ennominae), including their morphology, bionomic aspects and associated parasitoids. As a result, the areas presented a richness of Geometridae larvae equal to 496 individuals, where the species Phrygionis polita Cramer, 1780 and Argyrotome paraguayaria Schaus, 1927 presented greater abundance and higher parasitism index, respectively. Glyptapanteles sp. (Hymenoptera, Braconidae, Microgastrinae) and Euplectrus sp. (Hymenoptera, Eulophidae), with a gregarious habit, were the genera with the highest abundance of emerged adult parasitoids. While Casinaria spp. (Hymenoptera, Ichneumonidae, Campopleginae) presented greater diversity of morphospecies. Also, the first record of Distatrix flavus Rodrigues, Dias & Penteado-Dias, 2023 was obtained. Finally, the communities of both Geometridae larvae and their parasitoids present in the Cerrado Y of UFSCar, a preserved Cerrado area, showed greater diversity, consequently lower levels of equitability when compared to the communities of Geometridae larvae and their parasitoids present in the Trilha da Natureza, São Carlos, SP, Cerrado area recovering after fire.
Immature stages of Palyadini (Lepidoptera, Geometridae) and their parasitoids associated with Myrsine umbellata Mart. (Primulaceae) in Cerrado areas in São Carlos, SP
Keywords: Hymenoptera; Diptera; Mariposas; Larvas; Parasitoides; Moths; Caterpillars; Parasitoids; CIENCIAS BIOLOGICAS::ECOLOGIA